Improving Student Learning Outcomes Through the Picture and Picture Cooperative Learning Model - Muh. Asharif Suleman; Zulfi Idayanti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research aims to describe the application of the Picture and Picture Cooperative Learning Model and improve student learning outcomes after implementing this model. This type of research is Classroom Action Research (PTK), carried out over two cycles on class II elementary school students, totaling 24 students. Research procedures include planning, implementation, observation, evaluation, and reflection stages. Data collection uses observation, testing, and documentation techniques, which are then analyzed descriptively and qualitatively. The research results show that the implementation of the Picture and Picture Cooperative Learning Model has succeeded in increasing the activities of teachers and students. Teacher activity increased from 85.71% in cycle I to 95.23% in cycle II. Meanwhile, student activity increased from 79.16% in cycle I to 88.88% in cycle II. Student learning outcomes also experienced a significant increase. The average student score before the action was 51.21, with a learning completion level of 18.51%. After the actions in cycle I, the students' average score increased to 74.16, with a learning completion level of 70.83%. In cycle II, the students' average score increased to 82.08, with a learning completion level reaching 83.33%.